Serum IRAK3 may serve as a prognostic biomarker in acute supratentorial intracerebral hemorrhage: findings from a prospective observational cohort study - Ma, Yijun; Wang, Jun; Tang, Chao; Li, Wei; Lv, Xuan; Zhu, Suijun (Frontiers in Neurology, 2024)
Background: Interleukin-1 receptor-associated kinase 3 (IRAK3) modulates neuroinflammation. The purpose of this study was to discern the prognostic role of serum IRAK3 in acute intracerebral hemorrhage (ICH).In this prospective observational cohort study, 152 patients with supratentorial ICH, together with 63 healthy controls, were recruited. Serum IRAK3 levels were gauged at enrollment into the study in controls, at admission in all patients and at poststroke days 1, 3, 5, 7, 10 and 15 in 63 of those patients. National Institutes of Health Stroke Scale (NIHSS) and hematoma volume were utilized for estimating stroke severity. Poststroke 6-month modified Rankin Scale (mRS) scores were registered, with the scores of 3-6 representing a poor prognosis. Multivariate models were established to investigate severity correlation and prognosis association.Results: Serum IRAK3 levels were significantly elevated at admission of patients, peaked at day 1, plateaued at day 3 and thereafter gradually declined until day 15, and were substantially higher during poststroke fifteen days than in controls. Admission serum IRAK3 levels had an independent relation to NIHSS scores, hematoma volume and six-month mRS scores under multivariate linear regression model, were linearly correlated with risk of poor prognosis under restricted cubic spline, were independently predictive of poor prognosis under binary logistic regression model and exhibited efficient prognosis ability under receiver operating characteristic curve. Using subgroup analysis, no interactions were found between admission serum IRAK3 levels and some routine variables, such as age, gender, hypertension and diabetes mellitus. Also, the model, in which admission serum IRAK3, NIHSS scores and hematoma volume were merged, was comparatively stable and clinically valuable under calibration curve and decision curve. 3 3 Conclusion: A significant enhancement of serum IRAK3 levels during the early phase after ICH, in strong correlation with disease severity, is independently associated with poor six-month prognosis, substantializing serum IRAK3 as a valuable prognostic biomarker of ICH.